Herbal Medicine 2019
DOI: 10.5772/intechopen.72711
|View full text |Cite
|
Sign up to set email alerts
|

Application of Herbal Medicine as Proliferation and Differentiation Effectors of Human Stem Cells

Abstract: One of the main streams of traditional medicine is herbal medicine; a wide range of medicinal plants and their individual parts are used for therapy. Though not scientifically validated, this traditional medicine practice is much popular in countries such as India, China and Sri Lanka and in many other countries in South, Southeast and Eastern Asia due mainly to its healing capabilities. More recently, scientists initiated the chemical analyses of these medicinal plants, obtaining invaluable results. The lates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…and their bioactive compounds have received considerable attention because of their distinct pharmacology profiles, such as the rapid onset of action, less side effect profile, potential drug synergies, and most importantly because of their ability to improve proliferation, differentiation and therapeutic efficacy of stem cells [2,4,[12][13][14]. On the other hand, microarray gene expression profiling is a useful tool to explore genome-wide expression patterns that are activated during studied biological conditions and provides a foundation for further examination of molecular mechanisms and regulatory pathways.…”
Section: Agingmentioning
confidence: 99%
See 1 more Smart Citation
“…and their bioactive compounds have received considerable attention because of their distinct pharmacology profiles, such as the rapid onset of action, less side effect profile, potential drug synergies, and most importantly because of their ability to improve proliferation, differentiation and therapeutic efficacy of stem cells [2,4,[12][13][14]. On the other hand, microarray gene expression profiling is a useful tool to explore genome-wide expression patterns that are activated during studied biological conditions and provides a foundation for further examination of molecular mechanisms and regulatory pathways.…”
Section: Agingmentioning
confidence: 99%
“…Recent advanced researches on plant extracts and their bioactive compounds are bringing into light their importance in regenerative medicine. In this regard, several priming approaches using natural compounds have been proposed in recent years to activate stem cells for proliferation and differentiation and to improve the survival, function, and therapeutic efficacy of stem cells [12][13][14]. Moreover, recent evidence shows that the outcome of stem cell therapy in neurodegenerative diseases can be improved through the combination of adjunct treatments [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Biologically active compounds have been incorporated into stem cell research to maintain stem cell proliferation or to facilitate controlled differentiation into more defined tissues (Udalamaththa et al, 2016;Udagama and Udalamaththa, 2018;Saud et al, 2019). Our previous studies have suggested the potential of natural compounds in optimizing the microenvironment and regulating the early biological events to induce directed differentiation of hAESCs.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, natural resource-derived biologically active compounds, such as polyphenols, flavonoids, tannins, terpenoids, and fatty acids, have long been investigated for promoting cell division, and differentiation of pluripotent and adult stem cells (PSCs) under standard culture conditions (Udalamaththa et al, 2016;Udagama and Udalamaththa, 2018). Effects of plant extracts and their bioactive compounds on the proliferation and differentiation of mesenchymal stem cells (MSCs) have been extensively studied (Kornicka et al, 2017;Saud et al, 2019;Maeda, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, a new research stream has been evolving to use medicinal plant extracts as stimulants of stem cells because of their high availability, low toxicity, and minimum side effects (Udalamaththa et al, 2016;Kornicka et al, 2017;Udagama and Udalamaththa, 2018;Saud et al, 2019). However, despite the fact that hAECs were discovered decades ago, few researches have been done on using natural compounds to optimize the microenvironment or to regulate the early biological events for controlled differentiation of hAECs.…”
Section: Introductionmentioning
confidence: 99%